Fostering Environmental Culture Through Transformational Leadership and Teachers’ OCB - Luthfi Jusniar Dwiputri; Achmad Husen; Dian Alfia Purwandari; Zahra Nabilla; Bheni David Dwiana (Jurnal Indonesia Sosial Teknologi, 2025)
Environmental issues have become a critical agenda within the global education system, including in Indonesia, which has adopted environmental education through the Adiwiyata Program. However, fostering an environmentally conscious school culture cannot rely solely on programmatic initiatives; it requires visionary and participatory leadership. This research aims to examine how principals' transformational leadership can promote teachers’ Organizational Citizenship Behavior (OCB) as a catalyst for building a sustainable school culture. A descriptive qualitative method with a single case study design was employed, focusing on an elementary school located in the suburban area of Bogor Regency. Data were collected through in-depth interviews, participatory observation, documentation, and supplemented by closed-ended questionnaires. The findings reveal that the principal demonstrated key elements of transformational leadership—particularly idealized influence and intellectual stimulation—which significantly encouraged OCB among teachers, including proactive engagement in environmental initiatives and contributions to character development in students (e.g., care, discipline, and responsibility). These results align with existing literature, underscoring the interplay between transformational leadership, OCB, and the development of organizational culture. This research highlights the importance of integrating character-building into environmental education, enhancing ecologically oriented leadership development, promoting synergy between leadership and OCB, and reinforcing institutional policies that support sustainable environmental practices in schools.